Correlation between whole skeleton dual energy CT calcium-subtracted attenuation and bone marrow infiltration in multiple myeloma. Issue 149 (April 2022) - Gu, Renyang; Amlani, Ashik; Haberland, Ulrike; Hodson, Dan; Streetly, Matthew; Antonelli, Michela; Dregely, Isabel; Goh, Vicky; ,
Highlights: Quantification of whole skeleton calcium-subtracted attenuation with dual energy CT is feasible. Whole skeleton calcium-subtracted attenuation correlates with the degree of marrow infiltration by plasma cells on bone marrow biopsy. Whole skeleton calcium-subtracted attenuation provides complementary information to the detection of osteolytic bone lesions. Abstract: Objectives: Objective evaluation of the extent of skeletal marrow involvement in multiple myeloma remains a clinical gap for CT. We aimed to develop a quantitative segmentation pipeline for dual energy CT and to assess whether quantified whole skeleton calcium-subtracted attenuation values correlate with biopsy-derived bone marrow infiltration in multiple myeloma. Methods: Consecutive prospective patients with suspected/established myeloma underwent dual source CT from the skull vertex to proximal tibia. Whole skeleton segmentation was performed for 120 kVp-equivalent images as follows: following Hounsfield unit (HU) thresholding, a Chan-Vese morphological operation was implemented to generate a whole skeleton segmentation mask. This mask was then applied to corresponding whole skeleton material decomposition calcium-subtracted maps, generating whole skeleton HU values. Associations with biopsy-derived bone marrow plasma cell infiltration percentage were assessed with Spearman's rank correlation; significance was at 5%. Results: 21 patients (12 females; median (IQR) 67 (61, 73) years) were included; 16 patients had osteolytic bone lesions; 15 patients underwent bone marrow biopsy. Segmentation and quantification were feasible in all patients. Median (IQR) of the average skeletal calcium-subtracted attenuation was −59.9 HU (-66.3, −51.8HU). There was a positive correlation with bone marrow plasma cell infiltration percentage (Spearman's rho: + 0.79, p < 0.001 ). Conclusion: Whole skeleton calcium-subtracted attenuation is associated with the degree of bone marrow infiltration by plasma cells, providing an objective measure of marrow involvement with the potential to allow earlier detection of disease.